Semi‐automated digital quantification of cellular infiltrates for in vivo evaluation of transplanted islets of Langerhans encapsulated with bioactive materials. (4th July 2021) - Ramirez, Matias; Courtoy, Guillaume; Kharrat, Oumaima; de Beukelaer, Michele; Mourad, Nizar; Guiot, Yves; Bouzin, Caroline; Gianello, Pierre
Abstract: Background: In the field of xenotransplantation, digital image analysis (DIA) is an asset to quantify heterogeneous cell infiltrates around transplanted encapsulated islets. Materials and Methods: RGD‐alginate was used to produce empty capsules or to encapsulate neonatal porcine islets (NPI) with different combinations of human pancreatic extracellular matrix (hpECM), porcine mesenchymal stem cells (pMSC) and a chitosan anti‐fouling coating. Capsules were transplanted subcutaneously in rats for one month and then processed for immunohistochemistry. Immunostainings for macrophages (CD68) and lymphocytes (CD3) were quantified by DIA in two concentric regions of interest (ROI) around the capsules. DIA replicability and reproducibility were assessed by two blind operators. Repeatability was evaluated by processing the same biopsies at different time points. DIA was also compared with quantification by point counting (PC). Results: Methodology validation: different sizes of ROIs were highly correlated. Intraclass correlation coefficients confirmed replicability and reproducibility. Repeatability showed a very strong correlation with CD3 stains and moderate/strong for CD68 stains. Group comparisons for CD68 IHC at each time point proved internal consistency. Point counting and DIA were strongly correlated with both CD3 and CD68. Capsule biocompatibility: Macrophage infiltration was higher around capsules containing biomaterials than around empty and RGD‐alginate‐NPI capsules. Lymphocytic infiltration was comparable among groups containing cells and higher than in empty capsules. Conclusion: We validated a semi‐automated quantification methodology to assess cellular infiltrates and successfully applied it to investigate graft biocompatibility, showing that neonatal porcine islets encapsulated in alginate alone triggered less infiltration than capsules containing islets and bioactive materials.